Odpowiedzi

Najlepsza Odpowiedź!
2010-02-16T16:21:03+01:00
A) 2x²-10-3x²+6x+x²-2x=4x-10
b)a²+ab+ac-ba+b²-bc-ca+cb+c²=a²+b²+c²
c)x³+2x²+x+(4x³-8x²+6):2= x³+2x²+x+2x³-4x²+3= 3x³-2x²+x+3
2010-02-16T16:23:46+01:00
A) 2x (x-5) - 3 ( x²- 2x ) + (x-2) x =4x(do kwadratu) + 3x(do kwadratu) + 6x + x(do kwadratu) = 2x =4x(do kwadratu) + 6x


b)a(a + b +c)- b (a-b+c) - c (a-b-c) =a(do kwadratu)+ab+ac + ab+b(do kwadratu)-cb +ac +bc +c(do kwadratu)=a(do kwadratu)+b(do kwadratu) + c (do kwadratu)+2ab+2ac +2cb


c)x(x²+2x+1) - (-4x³ + 8x²- 6 ) ÷ 2 = x(do sześcianu) + 2x(do kwadratu) + x +4x(do sześcianu)+8x(do kwadratu) + 6 :2 =5x(do sześcianu)+10x(do kwadratu)+3